Integration by Stealth: How the European Union Gained Competence over Foreign Direct Investment*. (13th January 2017) - Meunier, Sophie
Abstract: How are policy competences allocated between different actors? This article contributes to the literature on institutional development through an in‐depth case‐study of the conditions under which the competence over the negotiation of agreements on foreign direct investment (FDI) was transferred from the national level to the European Union (EU) in the 2009 Lisbon Treaty. Most analysts assume that this competence shift was a rationally designed delegation, intended to maximize European bargaining power in international investment negotiations and conceived as an important element of a teleological drive to make the EU a meaningful external actor. This article tells a different story – one where the competence shift happened by stealth as a result of a combination of neo‐functionalist Commission entrepreneurship and historical accident, against the preferences of the Member States. The article also assesses whether the conditions under which the competence was transferred have implications for the implementation of the new policy.